2014
DOI: 10.1038/tp.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental toxicants and autism spectrum disorders: a systematic review

Abstract: Although the involvement of genetic abnormalities in autism spectrum disorders (ASD) is well-accepted, recent studies point to an equal contribution by environmental factors, particularly environmental toxicants. However, these toxicant-related studies in ASD have not been systematically reviewed to date. Therefore, we compiled publications investigating potential associations between environmental toxicants and ASD and arranged these publications into the following three categories: (a) studies examining esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
366
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(387 citation statements)
references
References 196 publications
6
366
0
6
Order By: Relevance
“…Additionally, environmental factors, such as exposure to toxicants, are associated with ASD and can result in inflammation and oxidative stress which, in turn, can result in mitochondrial dysfunction and damage to DNA and RNA [5]. Such environmental factors combined with a reduced availability of folate and glutathione can worsen mitochondrial function, cause methylation abnormalities and neurotransmitter depletion and limit the ability of the cells to repair damaged DNA.…”
Section: Folate Metabolism: An Example Of Environment-genome Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, environmental factors, such as exposure to toxicants, are associated with ASD and can result in inflammation and oxidative stress which, in turn, can result in mitochondrial dysfunction and damage to DNA and RNA [5]. Such environmental factors combined with a reduced availability of folate and glutathione can worsen mitochondrial function, cause methylation abnormalities and neurotransmitter depletion and limit the ability of the cells to repair damaged DNA.…”
Section: Folate Metabolism: An Example Of Environment-genome Interactionmentioning
confidence: 99%
“…A notion of a pure genetic etiology is tempered by the fact that single gene and chromosomal defects are found in a minority of ASD cases, accounting for only 15.8% of cases when both chromosomal microarray and whole exome sequencing were used in one recent large study [4]. ASD has also been associated with exposures to numerous environmental agents during the prenatal and postnatal period [5]. Studies that have examined the contribution of the environmental and genetic components highlight that ASD arises as a consequence of complicated interactions between genetic predisposition and environmental factors [6,7].…”
mentioning
confidence: 99%
“…It is important to say that a 4:1 male-to-female ratio in ASD has been widely recognized; thus, male-related hormonal factors may amplify the adverse effects of metals and contribute to the higher male prevalence observed in ASD (Rossignol et al 2014). A recent systematic review suggested genderrelated differences in the susceptibility to metals, with boys generally more susceptible than girls (Llop et al 2013).…”
Section: Discussionmentioning
confidence: 86%
“…Investigated therapeutic modalities include psychobehavioral therapies, 110 -115 psychopharmacology, 116 -118 occupational and language therapies, 119 -121 and complementary and alternative medicines. 122 Unfortunately, many studies have had methodologic limitations (eg, small sample sizes, variability in study populations, methods or interventions used, and outcomes measures) and are not applicable to the medical setting. 123 -125 Three evidence-based reviews of this topic conclude that there is adequate evidence for only a limited number of therapies (eg, pharmacotherapy), although several other strategies show promise (eg, early and intensive behavioral therapy, social skills training, and visual communication systems).…”
Section: Children With Special Needs Autism Spectrum and Developmentamentioning
confidence: 99%